2015
DOI: 10.1002/ccd.26234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and safety of dual antiplatelet therapy with or without warfarin in patients with a clinical indication for DAPT and chronic anticoagulation: A meta‐analysis of observational studies

Abstract: All-cause mortality appears similar in patients treated with TT or DAPT although TT was associated with higher rates of major bleeding and a lower risk for ischemic stroke. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
2
11
0
1
Order By: Relevance
“…In triple therapy patients older than 70 years, the bleeding rate in this study was in the 15‐28% range versus 0.0% in the sub‐septuagenarian age group. This, however, is also in agreement with recent findings by Bavishi et al who conducted a meta‐analysis of observational studies.…”
Section: Discussionsupporting
confidence: 93%
“…In triple therapy patients older than 70 years, the bleeding rate in this study was in the 15‐28% range versus 0.0% in the sub‐septuagenarian age group. This, however, is also in agreement with recent findings by Bavishi et al who conducted a meta‐analysis of observational studies.…”
Section: Discussionsupporting
confidence: 93%
“…1,7 Moreover, trials have shown that triple therapy after PCI is associated with a twofold increase in bleeding in the patients relative to double therapy, and post-PCI bleeding events are linked to worse MACE outcomes, possibly from the interruption in antithrombotic therapy during bleeding events. [28][29][30][31][32] It has been shown that double therapy is enough for most patients with AF, and ACS/ PCI and triple therapy may increase the risk of bleeding. 27,33,34 We have shown that double therapy with DOACs is safe and as effective as triple therapy with VKA.…”
Section: Discussionmentioning
confidence: 99%
“…22 Randomized clinical trials showed that TAT after PCI in AF patients is associated with twofold increased in the incidence of bleeding events compared with DAT. 3,23,24 In patients who experience significant bleeding events after PCI, antiplatelet and antithrombotic agents are sometimes partially or completely discontinued, that in turn, will increase the ischemic events. 25 Therefore, it is essential to identify patients with AF and ACS undergoing PCI who are at high risk for bleeding events, before starting the therapy with DAT or TAT.…”
Section: Guidance For Choosing Dat or Tat In Daily Clinical Practicementioning
confidence: 99%